2023
DOI: 10.1161/jaha.122.028198
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐Derived Neurotrophic Factor Precursor Contributes to a Proinflammatory Program in Monocytes/Macrophages After Acute Myocardial Infarction

Abstract: Background The imbalance of monocyte/macrophage polarization toward the preferential proinflammatory phenotype and a lack of normal inflammation resolution are present in acute myocardial infarction (AMI). Our previous study showed that upregulation of brain‐derived neurotrophic factor precursor (proBDNF) in M2‐like monocytes may contribute to the proinflammatory response in the Stanford type‐A acute aortic dissection. The present study aimed to investigate the role of proBDNF signaling in monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Third, we tried to investigate the pathogenesis of AMI at the cellular level and observed the differential composition of immune cells between patients with AMI and controls. Previous studies have reported that the percentage of monocytes, particularly proinflammatory monocytes, increases in AMI, 71,72 which is consistent with our study. Particularly, Li et al reported that MMP-9 activity played a pathogenic role in the imbalance of monocytes and macrophages in AMI.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Third, we tried to investigate the pathogenesis of AMI at the cellular level and observed the differential composition of immune cells between patients with AMI and controls. Previous studies have reported that the percentage of monocytes, particularly proinflammatory monocytes, increases in AMI, 71,72 which is consistent with our study. Particularly, Li et al reported that MMP-9 activity played a pathogenic role in the imbalance of monocytes and macrophages in AMI.…”
Section: Discussionsupporting
confidence: 94%
“…Particularly, Li et al reported that MMP-9 activity played a pathogenic role in the imbalance of monocytes and macrophages in AMI. 71 It is well established that macrophages participate in the development of atherosclerosis. Macrophages are divided into two polarized subsets: proinflammatory M1 and anti-inflammatory M2 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The different activities of macrophages originate from different subtypes and polarizations, showing a pro-in ammatory phenotype in the early stage and an anti-in ammatory phenotype in the late stage of AMI [29,30]. However, the early in ammatory response of the heart plays a vital role in later cardiac recovery and scar formation [31,32]. Therefore, targeted intervention with macrophages and monocytes may be bene cial for treating injury after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study revealed that endogenous proBDNF in proinflammatory monocytes/macrophages played a protective role by regulating MMP‐9 signaling in acute myocardial infarction (AMI). Administration of mAb-proB skewed monocytes/macrophages into a proinflammatory phenotype after AMI ( 35 ).…”
Section: Probdnf and Its Receptorsmentioning
confidence: 99%